PENGARUH SELF ESTEEM, SELF EFFICACY, LOCUS OF CONTROL, DAN EMOTIONAL STABILITY PADA KINERJA PENGELOLA ANGGARAN BELANJA UNIVERSITAS UDAYANA - Deany, Ary Sinar; Sukartha, I Made; Wirama, I Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The objective of this study is to determine the effect of self esteem, self efficacy, locus of control and emotional stability on the performance s of expenditure budget manager s at Udayana University. The realization of the budget in accordance with the target reflects the performance s success of expenditure budget manager s . This study t ook place at Udayana University and questionnaire technique is used as the method of data collection. Total samples in this study are 74 p ersons consists of commitment making officials, treasurer, auxiliary treasurer and headquarter’s financial staff. Data analysis technique in this study is multiple linear regression analysis. The results of the analysis show that all variables, i.e. self esteem, self efficacy, locus of control, and emotional stability are positively affect the performance s of expenditure budget manager s .
Keywords: Self Esteem, Self Efficacy, Locus Of Control, Emotional Stability, Performance of Expenditure Budget Manager